The Implication of A Divided or Unified Government for Public Policy Making: Indonesia During the Democracy Transition - Hutahaean, Marlan (SCAD Independent, 2017)
The purpose of this article is to delves the implications of a divided or unified government for public policy making in Indonesian democracy transition process. This article used qualitative methodology. Data which was collected during the early phases of the research process was analysed by using several descriptive analysis techniques.The authors found evidence that showed that the formation of a unified government during Gus Dur-Megawati, Megawati-Hamzah Haz, SBY-JK, and SBY-Boediono regimes did not translate into an easy public policy making process. The same is expected to apply to Jokowi-JK government. The existence of a divided government during Jokowi-JK regime continues hampering the policy making process. The existence of a divided or unified government does not have so much influence on the policy making process rather the substance of the policy, the level of support the government can garner in the national assembly.